Rituximab, a new treatment for difficult‐to‐treat chronic erythema multiforme major? Five cases. (15th September 2015) - Hirsch, G.; Ingen‐Housz‐Oro, S.; Fite, C.; Valeyrie‐Allanore, L.; Ortonne, N.; Buffard, V.; Verlinde‐Carvalho, M.; Marinho, E.; Martinet, J.; Grootenboer‐Mignot, S.; Descamps, V.; Wolkenstein, P.; et al.
Abstract: Background: Erythema multiforme major (EMM) is an inflammatory disease affecting skin and mucosae, often triggered by infection with Herpes simplex virus . Some patients have a chronic disease associated with antidesmoplakin autoantibodies, but the pathophysiology remains to be elucidated. First‐line treatment is antiviral therapy. With treatment failure or in patients without herpes‐triggered disease, thalidomide is effective but has neurological side‐effects. Alternatives (dapsone, immunosuppressant agents) are not codified. For many patients, systemic steroids use is chronic. The immunosuppressant drug rituximab (RTX) may be effective. Objectives: We report five cases of severe chronic EMM treated with rituximab (RTX). Methods: Five patients with severe chronic EMM for 9–20 years received RTX after failure or side‐effects of several treatments, especially antiviral therapy and thalidomide. All had chronic use of steroids. Four patients had antidesmoplakin autoantibodies. Results: Four patients experienced complete or quasi‐complete remission of EMM with withdrawal of steroids and one patient partial remission, for 3–11 months. Disease relapsed in all patients, and three received a second cycle of RTX with shorter duration of efficacy. Two patients received a third cycle, one without efficacy. Conclusion: The use of RTX for many autoimmune diseases, especially pemphigus, is increasing. Chronic EMM, especially EMM associated to antidesmoplakin autoantibodies, is an inflammatory disease in which the role of B cells is not well understood. However, we report a favourable benefit of RTX treatment for months in five patients with severe disease. RTX could be a therapeutic option in severe, difficult‐to‐treat EMM.